Evaluating the Role of Inflammation in Chronic Airways Disease: The ERICA Study. (1st September 2014) - Mohan, Divya; Gale, Nichola S.; McEniery, Carmel M.; Bolton, Charlotte E.; Cockcroft, John R.; MacNee, William; Fuld, Jonathan; Lomas, David A.; Calverley, Peter M. A.; Shale, Dennis J.; Miller, Bruce E.; Wilkinson, Ian B.; et al.
Abstract Extrapulmonary manifestations are recognized to be of increasing clinical importance in Chronic Obstructive Pulmonary disease. To investigate cardiovascular and skeletal muscle manifestations of COPD, we developed a unique UK consortium funded by the Technology Strategy Board and Medical Research Council comprising industry in partnership with 5 academic centres. ERICA (Evaluating the Role of Inflammation in Chronic Airways disease) is a prospective, longitudinal, observational study investigating the prevalence and significance of cardiovascular and skeletal muscle manifestations of COPD in 800 subjects. Six monthly follow up will assess the predictive value of plasma fibrinogen, cardiovascular abnormalities and skeletal muscle weakness for death or hospitalization. As ERICA is a multicentre study, to ensure data quality we sought to minimise systematic observer error due to variations in investigator skill, or adherence to operating procedures, by staff training followed by assessment of inter- and intra-observer reliability of the four key measurements used in the study: pulse wave velocity (PWV), carotid intima media thickness (CIMT), quadriceps maximal voluntary contraction force (QMVC) and 6-minute walk distance (6MWT). This report describes the objectives and methods of the ERICA trial, as well as the inter- and intra-observer reliability of these measurements.